Relationship of umbilical coiling index and cord twist direction with adverse perinatal outcomes - Sarkate, Pratibha S.; Hiwale, Sujitkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The main objectives of this study were to examine - (1) relationship of pregnancy-related factors (maternal age, gestational diabetes mellitus, pregnancy-induced hypertension, oligohydramnios, small for gestational age (GA), and fetal gender) and postnatally measured umbilical coiling index (UCI); (2) association of UCI and cord twist directions with the following adverse perinatal outcomes, meconium staining of amniotic fluid, non-reassuring FHR on CTG, low Apgar score (<7) at one and five minutes, low birth weight, and NICU admission. Methods: The inclusion criteria were singleton live-birth pregnancy with GA > 34 weeks. The cases were categorized in hypocoiled (UCI <10th percentile), hypercoiled (UCI >90th percentile) and normocoiled groups. To study relationship of pregnancy-related factors and UCI multivariate logistic regression was used; whereas bivariate analysis was used to study impact of UCI on various adverse perinatal outcomes. UCI was measured by a single observer. Results: In total, 100 subjects were enrolled. The mean UCI was 0.268 (SD = 0.13; 10th percentile = 0.139; 90th percentile =0.410) coils/cm. Pregnancy-related factors had non-significant relationship with UCI. For adverse perinatal outcomes, only the non-reassuring/abnormal FHR patterns were significantly associated with hypercoiled groups (OR = 4.5; CI= 1.15-17.58). Both the cord directions had almost equal distribution without any significant difference in outcomes; however, anticlockwise twisted cords were found to have significantly high UCI. Conclusions: No significant relationship was observed with pregnancy-related factors and UCI. However, it was observed that hypercoiled cords had significant association with non-reassuring/abnormal FHR patterns on CTG.